1993
DOI: 10.1016/0042-6989(93)90210-n
|View full text |Cite
|
Sign up to set email alerts
|

Focal visual attention produces illusory temporal order and motion sensation

Abstract: Spatial attention was studied using a new visual ilhrsion of motion: a line, which was presented physically at once, was perceived to be drawn from one side when attention had been captured to that side of the line by a preceding visual cue stimulus. By comparing with a temporal order task, we showed that the line-motion illusion was produced by acceleration of visual information processing at the locus of attention. The results suggest that the facilitatory effect of attention is exerted at relatively early s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
250
1
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(282 citation statements)
references
References 73 publications
26
250
1
4
Order By: Relevance
“…Observers reported a percept of the attended light appearing to come on before the unattended one. A similar account is given of the illusory line-motion phenomenon reported by Hikosaka et al (1993aHikosaka et al ( , 1993b in which a horizontal line, when presented in its entirety at one instant in time, appears to be drawn from the spatial location where the observer's attention was beckoned by the brightening of a dot. Thus the illusory line-motion results from a gradient of attentional facilitation that radiates in all directions from the cued location and weakens with distance (LaBerge 1983;LaBerge and Brown 1989;McCormick and Klein 1990;Stelmach and Herdman 1991;Stelmach et al 1994;Schmidt et al 1998;but see Downing and Treisman 1997).…”
Section: Attentional Accountmentioning
confidence: 91%
See 1 more Smart Citation
“…Observers reported a percept of the attended light appearing to come on before the unattended one. A similar account is given of the illusory line-motion phenomenon reported by Hikosaka et al (1993aHikosaka et al ( , 1993b in which a horizontal line, when presented in its entirety at one instant in time, appears to be drawn from the spatial location where the observer's attention was beckoned by the brightening of a dot. Thus the illusory line-motion results from a gradient of attentional facilitation that radiates in all directions from the cued location and weakens with distance (LaBerge 1983;LaBerge and Brown 1989;McCormick and Klein 1990;Stelmach and Herdman 1991;Stelmach et al 1994;Schmidt et al 1998;but see Downing and Treisman 1997).…”
Section: Attentional Accountmentioning
confidence: 91%
“…For instance, attentionally mediated improvements in performance can result from enhanced perceptual processing, differential capacity allocation, or internal noise reduction (Lu and Dosher 1998). In terms of enhanced visual processing, it has been suggested that attending to a spatial location facilitates processing of stimulus information at that site (Titchener 1908(Titchener /1973Posner and Petersen 1990;Hikosaka et al 1993aHikosaka et al , 1993bDesimone et al 1994;Shimojo et al 1995). Though the Posner (1980) cueing paradigm investigates what might be considered post-perceptual contributions to visual processing, such as the effects of expectation of a signal at a given location, cueing is generally characterized as leading to signal enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…Attention is also assumed to influence the speed at which information is transmitted through the visual system (11,12). However, since attention is a modulatory process, only comparisons between two perceptual outcomes, based either on overt behavioral responses or on subjective reports, would reveal the influence of attention (13). Thus, temporal order judgment tasks can provide a reliable psychophysical measure of changes in perceptual latency or in information transmission speed in the visual system (14).…”
mentioning
confidence: 99%
“…Further investigation on this topic, already in progress in our laboratory, might possibly shed some light on the interplay between sensory and attentional factors determining the perception of temporal order. Also, we hope that this effort might help us to understand other visual phenomena such as the flash-lag effect (17)(18)(19) and the perception of flicker, motion and other rapidly changing visual stimuli (13,20).…”
mentioning
confidence: 99%
“…In the experiments that follow, a blindsighted observer was tested using a version of the line motion illusion (25) entailing the reverse-phi phenomenon (26). For this stimulus, opposing motion directions are cued simultaneously by motion energy and changes in stimulus shape and position.…”
mentioning
confidence: 99%